Writing Voices: Aesthetic desublimation and narrative authority in Luigi Pirandello's Quaderni di Serafino Gubbio operatore and Italo Svevo's La coscienza di Zeno - Gatt-Rutter, John (Spunti e Ricerche, 2016)
The book was the first art form to lend itself to mechanical reproduction and to inaugurate mass culture and the democratization of knowledge. Both Pirandello and Svevo attempt to double the role of the novel as consumer product with its role as critique of a dehumanizing system of production and consumption. In the case of Pirandello, a subjective view, that of the author, is imposed as authoritative. Svevo systematically undermines any possible authoritarianism of fiction by presenting subjectivity itself, autonomous and unauthorized, denying final authority to any of his characters or to himself and delegating judgement and discrimination to his readers and to history.